Knowledge of nosocomial infection control practices among radiographers in Jordan. Issue 4 (November 2017) - Abdelrahman, M.A.; Alhasan, M.; Alewaidat, H.; Rawashdeh, M.A.; Al Mousa, D.S.; Almhdawi, K.A.
Abstract: Introduction: Nosocomial infections add health-related and financial burdens on health systems. This study aims to evaluate the radiographers' knowledge of nosocomial infection control practices in Jordan. Methods: A cross-sectional questionnaire-based assessment was conducted. The main domains of the knowledge based test were the nature of nosocomial infections, standard precautions, and infection control practices specific to the radiology department. Comparison of knowledge among radiographers was assessed using the Student t -test and ANOVA. Multiple linear regression was used to find predictors of the knowledge score. Results: The final analysis included 100 radiographers from educational, private, and public hospitals. Mean knowledge score was 66.2% (SD: 20.3%, range: 25.0–100%). Questions with the lowest correctly scored were about the main source of infections (17%), recapping used needles (27%), gloves use (27%), the necessity of using overshoes (26%) and a cap (26%) when there is a risk of biological fluid splashes, the necessity of using sterile gloves (7%) and protective masks (5%) during all invasive procedures, the manoeuvrability around a sterile field (54%), and the safety of passing the imaging plate to the scrub nurse in order to place it under the radiographer's direction (37%). Predictors of knowledge score were the academic degree and training status ( R 2 = 0.21, P < 0.001). Conclusion: Knowledge of infection control practices among Jordanian radiographers was moderate. Future training should focus on handling used needles, the use of protective barriers, and the manoeuvrability around sterile fields. Improved academic curriculum and on-site training could enhance knowledge in infection control practices. Highlights: Knowledge in infection control practices among Jordanian radiographers is moderate. Knowledge may be boosted through an improved academic curriculum and on-site training. Training should focus on managing needles, protective attire, and sterile fields.